Management of complicated gallstones in the elderly: comparing surgical and non-surgical treatment options - Nassar, Yousef (Gastroenterol Rep (Oxf), 2019)
OBJECTIVE: The aim of this study was to evaluate the differences in clinical outcomes of endoscopic retrograde cholangiopancreatography (ERCP), ERCP followed by cholecystectomy (EC) and percutaneous aspiration (PA) in the elderly population with choledocholithiasis. METHODS: We included a total of 43 338 elderly patients aged 60 years or older and 45 295 patients younger than 60 years for comparison in our study. Data were obtained from the Nationwide Inpatient Sample (Healthcare Utilization Project) for years 2001–14 by identifying patients who were admitted for gallstone complications based on the ICD 9 diagnostic code. Multiple logistic regression was used to calculate the odds of in-hospital mortality and to detect statistical differences among the treatment groups, age groups and between male and female patients. Univariate ordinary linear regression was used to compare the length of hospital stay and readmission frequency among the different age groups. RESULTS: The age of the patient affected mortality and the length of hospital stay after any type of procedure of gallstones removal. In a manner independent of the patient’s age, PA was associated with the highest risk of death and length of stay, while the EC was characterized by lowest mortality and ERCP by the shortest length of stay. Neither age of the patient nor the type of procedure affected the likelihood of readmission. The odds of death and the probability of readmission were not affected by patient sex. However, in patients aged between 60 and 79 years, the female gender predicted a shorter duration of stay in the hospital. CONCLUSIONS: A patient’s age negatively affects the treatment outcomes of cholelithiasis with associated complications. The EC procedure appears to be the method of choice for the management of complicated gallstones in patients of all ages.